Konstruksi Identitas Kultural Melalui Acara ‘Ngalor Ngidul Kalongan’ di Batik TV Pekalongan - Mubarok, Mubarok; Mulyadi, Urip; Triyono, Agus (Tuturlogi: Journal of Southeast Asian Communication, 2024)
This article will discuss the construction of Pekalongan cultural identity in the ‘Ngalor Ngidul Kalongan’ program on Batik TV Pekalongan. This program was chosen as a context to show how local content from the Local Public Broadcasting Institution (LPPL) constructs cultural identity. One of the differences with other studies on local content is the selection of television media and the concepts used. The concepts used are identity, cultural identity, local content and the role of local television. Batik TV was chosen as the object of research because of its position as an LPPL that differentiates its function and role from private television and TVRI. The method used is a literature study and observation of the Ngalor Ngidul Kalongan program broadcast on Batik TV Pekalongan. The literature study was conducted by selecting journal articles that are relevant to the research theme. Observations were made by reading broadcast descriptions and watching program content. The results of the study show that the construction of cultural identity appears in the program content which includes history, traditions, culinary, current community activities that are associated with the cultural identity of Pekalongan residents. The selection of the host and assistant host represents the figure of a cultural figure and the millennial young generation. This is to show the relationship between cultural materials and efforts to attract the interest of the millennial generation to watch the show. The construction of Pekalongan's cultural identity presented in the Ngalor Ngidul Kalongan show on Batik TV illustrates the characteristics of the behavior and way of thinking of 'Pekalongan people'. The show not only constructs identity from the aspect of type, but also commodifies it as a flagship show.